2004
DOI: 10.1136/ijgc-00009577-200401000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between histological criteria and human papillomavirus presence based on PCR assay in cervical biopsies

Abstract: The aim was to correlate histological findings in cervix lesions to human papillomavirus (HPV), as detected by polymerase chain reaction (PCR). One hundred and seven women with atypical Pap smear were submitted to colposcopic examination, and suspicious images were biopsied. The PCR assay was performed with the primers MY09/11 and GP05/06+ and, as control, the beta-globin gene was amplified. The morphological findings were correlated to HPV positivity: parakeratosis, acanthosis, koilocytotic atypia (KA), binuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Koilocytosis is considered a pathognomonic sign of HPV‐associated lesions . Although several authors have suggested an association between cytological and immunohistochemical positivity for HPV, others have found no morphological aspects that confirm the presence of HPV by polymerase chain reaction (PCR) . The prevalence of high‐risk HPV (16 and 18) in OSMF tissue has been reported in the literature .…”
Section: Discussionmentioning
confidence: 99%
“…Koilocytosis is considered a pathognomonic sign of HPV‐associated lesions . Although several authors have suggested an association between cytological and immunohistochemical positivity for HPV, others have found no morphological aspects that confirm the presence of HPV by polymerase chain reaction (PCR) . The prevalence of high‐risk HPV (16 and 18) in OSMF tissue has been reported in the literature .…”
Section: Discussionmentioning
confidence: 99%
“…nosis of HPV infection has certain limitations and do not correlate completely with viral detection by molecular assays (Salvia et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a false‐positive rate of 5–15%. ( 6–8 ) To carry out HPV genotyping, a reliable, FDA‐approved test to distinguish the specific HPV types will need to be developed and validated. A DNA‐based technology, the Hybrid Capture II HPV test, has been used to detect 13 high‐risk types of HPV.…”
mentioning
confidence: 99%